2020
DOI: 10.32479/ijeep.8970
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Integration Among Oil Exporter Countries: Testing Kenen’s Product Diversification Hypothesis in the Organization of Islamic Cooperation

Abstract: Kenen (1969) hypothesizes that countries that are largely dependent on one export commodity could experience weaker monetary integration and synchronize the business cycle among them. This paper aims to retest Kenen's hypothesis, which is applied to the seven largest oil-producing countries in the Islamic world. This study employs the optimum currency area index and the Pearson correlation matrix to determine the degree of integration and synchronization of the business cycle. This study empirically proves tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Perubahan harga minyak dunia, nilai tukar, dan inflasi terhadap neraca perdagangan di setiap negara mengalami perubahan yang berbeda bergantung pada kebijakan serta sistem pemerintah yang dianut oleh suatu negara (Agustiar, 2020). Negara Malaysia, Brunei Darussalam, Saudi Arabia, dan Indonesia yang memiliki sistem pemerintahan berbeda, hal ini menjadi menarik untuk dilakukan analisis yang terjadi apabila harga minyak dunia, nilai tukar, dan inflasi mengalami perubahan terhadap neraca perdagangan masing-masing negara.…”
Section: Pendahuluanunclassified
“…Perubahan harga minyak dunia, nilai tukar, dan inflasi terhadap neraca perdagangan di setiap negara mengalami perubahan yang berbeda bergantung pada kebijakan serta sistem pemerintah yang dianut oleh suatu negara (Agustiar, 2020). Negara Malaysia, Brunei Darussalam, Saudi Arabia, dan Indonesia yang memiliki sistem pemerintahan berbeda, hal ini menjadi menarik untuk dilakukan analisis yang terjadi apabila harga minyak dunia, nilai tukar, dan inflasi mengalami perubahan terhadap neraca perdagangan masing-masing negara.…”
Section: Pendahuluanunclassified
“…High levels of consumer prices (high inflation) lead to lower real incomes and domestic demand, higher unemployment (Hunt et al, 2001;Nordhaus, 2002;Abosedra and Baghestani, 2004), instability in the stock market, money market and foreign exchange market. causes (Krichene, 2008;Abhyankar et al, 2013;Agustiar, 2020).…”
Section: Oil Prices and Key Macroeconomic Indicatorsmentioning
confidence: 99%
“…Entrepreneurship could play an effective role on regional innovations and would accelerate the economic and industrial diversification (Grillitsch and Asheim, 2018;Xiao et al, 2018), would help the structural changes and diversification process in a country (Neffke et al, 2018) and could accelerate the knowledge spillovers and exports diversification (Chatmi and Elasri, 2018). Agustiar (2020) argued that export diversification may be harmful for monetary integration. He investigated this issue for the 7-oil producing countries and found that export concentration in these countries was not harmful for their monetary integration due to their strong economic structures.…”
Section: Literature Reviewmentioning
confidence: 99%